1995
DOI: 10.1073/pnas.92.3.763
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E is a kinetic but not a thermodynamic inhibitor of amyloid formation: implications for the pathogenesis and treatment of Alzheimer disease.

Abstract: The apolipoprotein E4 (APOE4) allele is associated with an early age of onset of the nonfamilial form of Alzheimer disease (AD) and with increased 8 protein amyloid deposition in the brain. These two observations may both arise from an effect of the apoE family of proteins on the rate of in vivo amyloidogenesis. We report here that apoE3, the common apoE isoform, is an in vitro amyloid nucleation inhibitor at physiological concentrations. A significant delay in the onset of amyloid fibril formation by the ,3-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
242
1
2

Year Published

1996
1996
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 334 publications
(268 citation statements)
references
References 28 publications
23
242
1
2
Order By: Relevance
“…ApoE has been demonstrated to modulate Ah clearance and fibrillogenesis both in vitro (Beffert et al, 1999;Castano et al, 1995;Evans et al, 1994;Koistinaho et al, 2004;Ma et al, 1994;Yang et al, 1997Yang et al, , 1999 and in vivo (Bales et al, 1997;DeMattos et al, 2004;Holtzman et al, 2000;Shibata et al, 2000). In vivo, human apoE suppresses the onset of Ah deposition and subsequently results in an isoform-specific effect (E4 N E3 N E2) on the amount of Ah deposition, fibril formation, and neuritic plaque formation Holtzman et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ApoE has been demonstrated to modulate Ah clearance and fibrillogenesis both in vitro (Beffert et al, 1999;Castano et al, 1995;Evans et al, 1994;Koistinaho et al, 2004;Ma et al, 1994;Yang et al, 1997Yang et al, , 1999 and in vivo (Bales et al, 1997;DeMattos et al, 2004;Holtzman et al, 2000;Shibata et al, 2000). In vivo, human apoE suppresses the onset of Ah deposition and subsequently results in an isoform-specific effect (E4 N E3 N E2) on the amount of Ah deposition, fibril formation, and neuritic plaque formation Holtzman et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…To date, while the effects of apoE on Ah clearance have been seen in in vitro and in vivo studies, an isoform-specific effect of apoE has been difficult to identify (DeMattos et al, 2004;Koistinaho et al, 2004). Some in vitro studies do show differential effects of apoE isoforms on Ah fibrillogenesis (E4 N E3) with some studies demonstrating that apoE inhibits and others showing apoE enhances Ah fibril formation (Castano et al, 1995;Evans et al, 1994;Ma et al, 1994). Importantly, while lipidated apoE has been used in some Ah binding and association studies (LaDu et al, 1994(LaDu et al, , 1995Tokuda et al, 2000), lipidated apoE has not been extensively utilized in studies examining the effect of apoE on Ah clearance and fibrillogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…formation at the time of analysis, (b) the concentration of A/I and amybid plaque component used, and (c) the time of analysis following incubation of A/I with a particular amybid plaque component. For example, a number of studies suggested that ApoE is a potent enhancer of A/I amyloid fibril formation (Soto et al, 1995, whereas others implicated ApoE as an A/I amyloid inhibitor (Evans et al, 1995;Ohman et a!., 1996). In some of these studies, it was clear that the ApoE isoform (e.g., ApoE3 versus ApoE4) was important for the observed enhancement or inhibitory effects.…”
Section: Discussionmentioning
confidence: 99%
“…E3 . E2) (Ma et al 1994;Wisniewski et al 1994;Castano et al 1995), whereas others show that apoE inhibits fibrillization (Evans et al 1994;Wood et al 1996). Conflicting results between in vitro studies may be owing to the differences in apoE and Ab preparations or other factors.…”
Section: Genetic Clinical and Biomarker Observations On Relationshimentioning
confidence: 99%